Export Promotion Agencies and Programs; Implications for policy makers of technology-based firms' export - mohsen rahimzadeh; Alireza naimi; Amir Zakery (سیاست نامه علم و فناوری, 2022)
Export promotion and support for the internationalization of enterprises is always on the public agenda. Export promotion programs are among the policies implemented to remove barriers to the presence of companies especially small and medium-sized companies in international markets. Although the export of technology-based products currently accounts for a small share of the country's exports, but due to the development of the ecosystem of technology-based firms in recent years and the relative success of these companies in meeting the country's needs, these companies have the potential to enter global markets; which is very important for their survival. This article provides a comprehensive overview of studies in the field of export promotion programs and the features and main components of these programs. By presenting a thematic classification of the studies, this study will examine the dimensions of the level of development of societies, functions and management and financial structure of these agencies, efficiency and effectiveness of programs and specific requirements of high technology products. Five main decision-making areas in the field of support programs have been identified: the level of awareness of export development programs, support based on the size or export experience of the company, the level of private sector participation in the board of export promotion agencies, and finally the presence of active diplomatic representatives. Finally, in order to improve the current knowledge of managers, the implications of the studies conducted for export policy makers of technology-based firms will be presented.